Methods for Achieving Cognitive, Affective, and Psychomotor Aspects in Islamic Religious Education Learning: A study at Senior High School in Rejang Lebong - Guntur Gunawan; Putri Rama Yanti; Nelson Nelson (AL-ISHLAH: Jurnal Pendidikan, 2023)
Learning which is the domain of education in the cognitive (knowledge), affective (attitude), and psychomotor (skills) aspects, is still the reference and the target of learning outcomes, including the learning process of Islamic Religious Education (PAI) in Senior High School in Rejang Lebong. This research is qualitative. Therefore, the author takes a descriptive approach, which is carried out because this author occurs authentically and naturally. The subject of study is the Principal, PAI subject teacher, and 30 students. The data collection technique is done by interview, observation, and documentation. According to the findings of this study, the educational process consists of three main elements: intake, processing, and output. Students from varied backgrounds are the input in question. The process is a learning activity in which the instructor provides and students grasp the content. Several educators measure emotional features in various methods, including monitoring students during teaching and learning. The affective aspect refers to the emotional or feeling aspect. The mass media provide emotional stimulation to the audience, giving rise to various feelings for each individual.